Sino ako?. com a multi-method study on the self concept of Filipino young adults and new communication technology - Agbayani II, Rafael C.; Lacson, Jose R. (Quezon City College of Mass Communication, University of the Philippines Diliman, 1998)
This study aimed to determine how the self-concepts of Filipino young adults relate with the way they use new communication technologies. Self-concept was defined as the relatively stable set of perceptions one holds for oneself based on self-description and social interaction and comparison. The communication technologies under study were the pager, cellular phone, the Internet, cable television and multimedia computers. Multi-methodologies approached the topic from both qualitative and quantitative paradigms. Focus interviews of eight informants and a one-shot survey of eighty-six respondents were conducted to fulfill the data requirements of this multi-method study. Findings show that Filipino young adults have multifaceted self-concepts as a result of their interaction with the society. Filipino young adults regard themselves most as friends before anything else. However they still derive much of their social support from their families. They regard being a family member as a given and not something to be but something they already are. Thus their self-concepts are more towards other social roles such as being a good friend, a diligent student, a career-oriented professional and a passionate lover. The multifaceted self-concepts of Filipino young adults give rise to various natures of communication needs. This in turn can be satisfied by at least one new communication gadget available. The pervasiveness of these technologies made them aware and knowledgeable of these gadgets whatever their self-concept may be. As a result, attitudes towards these technologies in general are positive. Filipino young adults perceive new communication technologies as convenient and fast. Covenient, like the way they like their friendships and fast, the way they like work should be done. Pagers proved to be the most flexible communication tool used by young adults. It handled short messages ranging from greetings, impersonal reminders to romantic quotes. Cellular phones were used mainly for emergency two-way pager in terms of frequency and type of messages. E-mailing to friends and family was the most popular use of the Internet. Information downloaded was for specialized personal needs. Cable television was mainly viewed for foreign movies and talkshows, showing Filipino young adults inclination for social comparison and opinion formulation. Finally multimedia computers were used for interactive games and desktop publishing. The variety of users of new communication technology made it a part of the lives of Filipino young adults of all kinds of self-concepts. This study found out that Filipino young adults' decision to use any of the media was almost certain as long as the technology is affordable and accessible. Filipino young adults are adaptive technology-users who would always find a specialized use of the media and reinforce their self-concepts.
Vita
Thesis
Keywords: Self-perception in adolescence -- Philippines; Mass media and young adults -- Philippines; Social media -- Philippines